If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18y = -20 + 19y Solving 18y = -20 + 19y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-19y' to each side of the equation. 18y + -19y = -20 + 19y + -19y Combine like terms: 18y + -19y = -1y -1y = -20 + 19y + -19y Combine like terms: 19y + -19y = 0 -1y = -20 + 0 -1y = -20 Divide each side by '-1'. y = 20 Simplifying y = 20
| -17-4k=3k+13-5k | | 0=-7r-3r | | 3(2x+5)=-37+22 | | 29=8+3x | | 25(x^2)-20x+4=0 | | 3g+9=4g | | 10-7k=-(8k-7) | | 8-9z=-5z | | 5-3(X-4)=11 | | -8=6(v-4)-8v | | -34+4p=-7(8+p) | | 7x-44=10-5x | | 0=7+5x^2-2x^3 | | 5+6h=-5+5h | | 4/5t+1=t+1/2 | | -3j-4j-1=-3j+7 | | 34=-8y+6(y+8) | | 16=p-5p | | -10-2n=-n | | 8n=7n-3 | | y=x^6-7x | | 9d=9+10d | | 4x^2-35x-414= | | 3w+15=48 | | 10B+8=68 | | -5(r+4)=-72 | | 10-7r=8-9r | | 2.4k=18.96 | | 4x^2+35x-414= | | 10y-12=48 | | 5(x+6)-7x=26 | | 3w+13=34 |